Q: -2x plus 3y equals 9

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2x + 3y = 9x = 3, y = 1 therefore 6 + 3 = 9

(-1,-2)

x = 8, y = -1

x + y = -2 2x + 3y = -9 You solve this by elimination - multiply both sides of first equation by 3, then subtract, solve for x, then substitute in any of the equations to solve for y 3x + 3y = -6 2x + 3y = -9 subtracting, x = 3 substituting into 1st equation, y = -2-3 = -5

It is -9

Related questions

2x + 3y = 9x = 3, y = 1 therefore 6 + 3 = 9

(-1,-2)

x = 8, y = -1

6x+3y = -9 3y = -6x-9 y = -2x-3 Therefore the perpendicular slope is 1/2

x + y = -2 2x + 3y = -9 You solve this by elimination - multiply both sides of first equation by 3, then subtract, solve for x, then substitute in any of the equations to solve for y 3x + 3y = -6 2x + 3y = -9 subtracting, x = 3 substituting into 1st equation, y = -2-3 = -5

The ordered pair is (-1, -2).

Put in function, Y = mX + C, form. 6X + 3Y = - 9 3Y = - 6X - 9 Y = - 2X - 3 -------------------- m(slope) = - 2 ----------------------

It is -9

-4x + 3y = 9

2x - 3y = 5 => 3y = 2x - 5 has a gradient of 2/3 9y + bx = 4 => 9y = -bx + 4 has a gradient of -b/9 The two gradiends must be the same if the two lines are parallel: 2/3 = -b/9 so that b = -6

6x + 3y = -9 So 3y = -6x - 9 or y = -2x - 3 So the slope of the given line is -2 Therefore, the slope a any parallel line is also -2.

3y = 4x + 9 -4x + 3y = 9 is the standard form